Answer:
x = -14
Step-by-step explanation:
Step 1: Write equation
4(x + 2) = 3(x - 2)
Step 2: Solve for <em>x</em>
- Distribute: 4x + 8 = 3x - 6
- Subtract 3x on both sides: x + 8 = -6
- Subtract 8 on both sides: x = -14
Step 3: Check
<em>Plug in x to verify it's a solution.</em>
4(-14 + 2) = 3(-14 - 2)
4(-12) = 3(-16)
-48 = -48
Answer:
y = 2
Step-by-step explanation:
The mid segment HJ is half of the third side GK , that is
HJ =
GK , substitute values
2y =
(y + 6) ← multiply both sides by 2 to clear the fraction
4y = y + 6 ( subtract y from both sides )
3y = 6 ( divide both sides by 3 )
y = 2
Answer:
E. 5
Step-by-step explanation:
Let's rewrite the equation in the form of y=mx+b, where m is the slope and b is the y-intercept (the value of y when x = 0).
2x + y = 5
y = -2x+5
M, the slope, is -2
<u>5, b, is the y-intercept</u>
See attached graph.
To solve this, first we calculate all the total cost of
the items that is:
total cost = $14.96 + $19.87 + $5.37
total cost = $40.20
So we see that the actual cost is similar with the
estimate so his calculation is reasonable.